Fragmentation Analysis of Plasma DNA Reveals Its Prognostic Value in Gastric Cancer - Yoruker, Ebru Esin; Ozgur, Emre; Keskin, Metin; Ozgur, Ilker; Gezer, Ugur (Turkish Journal of Gastroenterology, 2021)
Background: Gastric cancer (GC) is a common cause of cancer-related deaths. The poor clinical outcome in GC patients is partiallyassociated with a lack of appropriate diagnostic and prognostic biomarkers. In the present study, we evaluated the diagnostic andprognostic values of cell-free DNA (cfDNA) integrity and the concentration of circulating nucleosomes (cNUCs).Methods: In the study, 40 GC patients and 55 GC-free individuals were enrolled. Cell-free DNA integrity was calculated as the ratio ofconcentration of the longer ACTB (beta-actin) gene fragment to that of the shorter ACTB fragment, measured using quantitative PCR.Circulating nucleosomes were measured by an ELISA-based approach.Results: We found that cfDNA integrity is higher in GC patients than in the control subjects (relative median values 0.51 vs. 0.38, respectively,P = .56) indicating prominent abundance of longer fragments in the patients. The patients with larger tumors (T3-4) had significantlyhigher cfDNA integrity than those with T1-T2 tumors. We also found GC patients to have higher concentrations of cNUCs in theirplasma (relative median values 3.64 vs. 3.1). Importantly, the patients with high cfDNA integrity (i.e., lower fragmentation) had longeroverall survival rates at 3 years than those with lower cfDNA integrity (76.5% vs. 38.9%, P = .02).Conclusion: Cell-free DNA fragmentation has a prognostic value. However, it has no diagnostic value in GC.